Novel carbamate-linked quaternary ammonium lipids containing unsaturated hydrophobic chains for gene delivery. Issue 12 (23rd July 2018) - Zhou, Hengjun; Yang, Jian; Du, Yanyan; Fu, Shuang; Song, Chenxi; Zhi, Defu; Zhao, Yinan; Chen, Huiying; Zhang, Shubiao; Zhang, Shufen
Graphical abstract: Highlights: This work designed cationic lipids with unsaturated hydrophobic chains of C18:1. Gemini cationic liposome bearing C18:1 chains showed strong DNA binding ability. Gemini cationic liposome with C18:1 chains had a highest transfection efficiency. Gemini cationic liposome containing C18:1 chains showed low cytotoxicity. Abstract: In this paper, two novel carbamate-linked quaternary ammonium lipids (MU18: a lipid with a mono-ammonium head; GU18: a lipid with a Gemini-ammonium head) containing unsaturated hydrophobic chains were designed and synthesized. The chemical structures of the synthetic lipids were characterized by infrared spectrum, ESI-MS, 1 H NMR, 13 C NMR, and HPLC. For investigating the effect of unsaturation on gene delivery, the previous reported saturated cationic liposomes (MS18 and GS18) were used as comparison. Cationic liposomes were prepared by using these cationic lipids and neutral lipid DOPE at the molar ratio of 1:1. Particle sizes and zeta potentials of the cationic liposomes were studied to show that they were suitable for gene transfection. The binding abilities of the cationic liposomes were investigated by gel electrophoresis at various N/P ratios from 0.5/1 to 8/1. The results indicated that the binding ability of GU18 was much better than MU18 and the saturated cationic liposomes (MS18 and GS18). DNA transfection of these liposomes comparable to commercially available reagent (DOTAP) was achieved in vitro against Hela, HepG-2 and NCI-H460 cell lines. GU18 showed higher transfection at the N/P ratio of 3/1 than other cationic liposomes and the positive control, DOTAP. All of the liposomes presented a relatively low cytotoxicity, which was measured by MTT. Therefore, the synthetic lipids bearing unsaturated hydrophobic chains and Gemini-head could be promising candidates for gene delivery.